Study The Microbial Content for Some Cafeterias and Restaurants Foods in Babil Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to investigate  the microbiological  contamination of  some solid food  in the cafeterias and restaurants in some areas of Babil province, which included restaurants of the first class and other levels, rice, red meat, chicken meat, bread, biscuits and juices were collected for the period from November 2016 to February 2017. This study, through the microbiological analysis of the most consumed food in the cafeterias and restaurants that were studied in the areas of Alexandria and the modern village and the districts of  Mahaweel, Masib and Hilla.In vitro culturing  of food samples and biochemical tests of  bacteria on culture media, Escherichia coli was found, Staphylococcus epidermidis, Staphylococcus aureus, Salmonella typhi, Shigella dysentriae and some fungi on their culture media.The study also showed that cooked foods loaded by alower   germs than fresh foods. The results also showed that the foods used in restaurants are less than a microbial load of cafeterias. This study highlights the level of microbial content found in different foods available in cafeterias and restaurants.